2015
DOI: 10.1080/15384101.2015.1030548
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 1 (α, δ and ε) localize at the spindle poles, but may not be essential for mammalian oocyte meiotic progression

Abstract: CK1 (casein kinase 1) is a family of serine/threonine protein kinase that is ubiquitously expressed in eukaryotic organism. CK1 members are involved in the regulation of many cellular processes. Particularly, CK1 was reported to phosphorylate Rec8 subunits of cohesin complex and regulate chromosome segregation in meiosis in budding yeast and fission yeast. (1-3) Here we investigated the expression, subcellular localization and potential functions of CK1α, CK1δ and CK1ε during mouse oocyte meiotic maturation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…The CK1α protein expression profile was consistent with the profile of mRNA levels except for GV [33]. The protein expression level of CK1δ and CK1ε were same as CK1α, relatively low at GV stages and then gradually increased at MI and MII stages [34].…”
Section: Expression and Subcellular Localization Of Ck1supporting
confidence: 69%
See 1 more Smart Citation
“…The CK1α protein expression profile was consistent with the profile of mRNA levels except for GV [33]. The protein expression level of CK1δ and CK1ε were same as CK1α, relatively low at GV stages and then gradually increased at MI and MII stages [34].…”
Section: Expression and Subcellular Localization Of Ck1supporting
confidence: 69%
“…Furthermore, overexpression of exogenous CK1α, CK1δ and CK1ε, both individually and simultaneously, caused little effect on eitherthe meiosis process, spindle organization or chromosome alignment. Their report demonstrate that although CK1α, CK1δ and CK1ε were all localized to MTOCs or spindle poles, they were not the kinase responsible for Rec8 phosphorylation during mouse oocyte meiosis, indicating that CK1 was probably not essential for mouse oocyte meiotic maturation [34]. The contradictory results need further investigation.…”
Section: The Role Of Ck1 Isoforms In Meiosismentioning
confidence: 95%
“…[Ca 2+ ] m levels were assessed using Rhod-2AM (Invitrogen/Molecular Probes, Carlsbad, CA, U.S.) according to a previous study [ 20 ]. Briefly, zona pellucid was enzymatically removed.…”
Section: Methodsmentioning
confidence: 99%
“…siRNAs were microinjected into oocytes as described previously [ 20 ]. To knockdown Itpr1 or Pacs-2 , 10 μmol/L of each siRNA smart pool (a mixture of four siRNAs) or NC siRNA (GE Healthcare Life Sciences, South Logan, UT, U.S.) was used and the microinjection was completed within 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…For the effect of CK1 on oocyte meiosis, it had been claimed that inhibiting the expression of CK1 would lead to the failure of meiosis (Wang et al, ). However, there was a report indicated that the lack of CK1 increased the duration of meiosis and did not stop meiosis (Qi et al, ).…”
Section: Introductionmentioning
confidence: 99%